(untitled) (Research Announcements "Heritage BG", 2025)
The appearance of the literary dictionary in Bulgaria was registered between the two world wars, when the concept ofliterary history was already a fact. Literary historyliterary history seeks to cover the whole literary life and process, or to approach conceptually, selectively, taking into account the diversity of ideas, aesthetics and stylistics. In contrast, the dictionary strives for a smaller or larger scale, comprehensiveness of names and phenomena, completeness ofliterary-historical knowledge, although it uses the means of analytical-synthetic exposition. In the history of Bulgarian literary dictionaries, the dictionary either continued the literary-historical narrative by other means, or supplemented and compensated the lack of adequate literary-historical knowledge, or used new possibilities for structuring this knowledge in its special format. References: Mirolyubov 1907: Mirolyubov, V. [D-r K. Krastev]. Vmesto predgovor. In: Mirolyubov, V. Mladi i stari. Kriticheski ocherki varhu dneshnata balgarska literatura. Penev 1910: Penev, Boyan. Posoki i tseli pri prouchvane na novata ni literatura. In: Lit. sb. ‘Misal’, 1-32. Sivriev 1999: Sivriev, Sava. Mitos i tehne. Opit varhu balgarskata literatura ot minaliya vek. Sofiya. Strashimirov 1896: Strashimirov, D. T. [[‘Balgarska literatura’. Ot A. Teodorov]. – Balgarska sbirka, 5, 496-508.] Teodorov-Balan 1896: Teodorov-Balan, Aleksandar. Balgarska literatura. Kratko rakovodstvo za sredni i spetsialni uchilishta. Plovdiv: Izdanie i pechat na Hr. G. Danov.